Autophagy, Pyroptosis, and Ferroptosis: New Regulatory Mechanisms for Atherosclerosis - Lin, Lin; Zhang, Mu-Xin; Zhang, Lei; Zhang, Dan; Li, Chao; Li, Yun-lun (Frontiers in Cell and Developmental Biology, 2022)
Atherosclerosis is a chronic inflammatory disorder characterized by the gradual buildup of plaques within the vessel wall of middle-sized and large arteries. The occurrence and development of atherosclerosis and the rupture of plaques are related to the injury of vascular cells, including endothelial cells, smooth muscle cells, and macrophages. Autophagy is a subcellular process that plays an important role in the degradation of proteins and damaged organelles, and the autophagy disorder of vascular cells is closely related to atherosclerosis. Pyroptosis is a proinflammatory form of regulated cell death, while ferroptosis is a form of regulated nonapoptotic cell death involving overwhelming iron-dependent lipid peroxidation. Both of them exhibit distinct features from apoptosis, necrosis, and autophagy in morphology, biochemistry, and genetics. However, a growing body of evidence suggests that pyroptosis and ferroptosis interact with autophagy and participate in the development of cancers, degenerative brain diseases and cardiovascular diseases. This review updated the current understanding of autophagy, pyroptosis, and ferroptosis, finding potential links and their effects on atherogenesis and plaque stability, thus providing ways to develop new pharmacological strategies to address atherosclerosis and stabilize vulnerable, ruptured plaques.